A study of the interactions between human osteoblast-like cells and polymer composites with functionalized graphene derivatives using 2D correlation spectroscopy (2D-COS) - Kołodziej, Anna; Wesełucha-Birczyńska, Aleksandra; Długoń, Elżbieta; Świętek, Małgorzata; Gubernat, Maciej; Skalniak, Łukasz; Błażewicz, Marta (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
In response to the growing need for development of modern biomaterials for applications in regenerative medicine strategies, the research presented here investigated the biological potential of two types of polymer nanocomposites. Graphene oxide (GO) and partially reduced graphene oxide (rGO) were incorporated into a poly(ε-caprolactone) (PCL) matrix, creating PCL/GO and PCL/rGO nanocomposites in the form of membranes. Proliferation of osteoblast-like cells (human U-2 OS cell line) on the surface of the studied materials confirmed their biological activity. Fluorescence microscopy was able to distinguish the different patterns of interaction between cells (depending on the type of material) after 15 days of the test run. Raman micro-spectroscopy and two-dimensional correlation spectroscopy (2D-COS) applied to Raman spectra distinguished the nature of cell-material interactions after only 8 days. Combination of these two techniques (Raman micro-spectroscopy and 2D-COS analysis) facilitated identification of a much more complex cellular response (especially from proteins) on the surface of PCL/GO. The presented approach can be regarded as a method for early study of the bioactivity of membrane materials.
Keywords: polymery; polyestery; Polymer nanocomposite; grafit; Polymers; Poly(ε-caprolactone) (PCL); lidé; Osteoblasts; Ramanova spektroskopie; 2D correlation spectroscopy (2D-COS); Raman micro-spectroscopy; Reduced graphene oxide (rGO); Polyesters; Graphene oxide (GO); Humans; Graphite; osteoblasty; Spectrum Analysis, Raman